Evaluation of an alternative indirect-ELISA test using in vitro-propagated Trypanosoma brucei brucei whole cell lysate as antigen for the detection of anti-Trypanosoma evansi IgG in Colombian livestock (2019)
Surra is a zoonotic disease caused by Trypanosoma evansi, affecting the health and production of the livestock significantly. There are several methods to diagnose this disease, which have different principles, sensitivity, and specificity. Among them, the serological techniques using T. evansi as antigen are powerful tools for its epidemiological surveillance. However, they are poorly used due to inefficient in vitro propagation of T. evansi, which requires the use of laboratory animals for antigen production. In the present study, whole cell lysate of T. brucei brucei propagated in vitro was used as an antigen for the detection of anti-T. evansi immunoglobulin G in cattle through an indirect-ELISA. Based on a total of 45 samples from non-infected and 45 samples from T. evansi infected cattle, the sensitivity and specificity were estimated as 100% and 97.7%, respectively. After the validation, serological and molecular surveys were carried out in 710 cattle samples from two endemic Colombian regions (Antioquia and Arauca departments) for T. evansi where molecular prevalences of ˜7.0% were detected through the year and sporadic outbreaks of T. vivax infections have been associated to low prevalence of this species (<1%). A total of 424 (59.7%) samples were positive by indirect-ELISA T. b. brucei, while PCR test for T. evansi and T. vivax, showed 49 (6.9%) and no positive samples, respectively. Interestingly, categories of animals aged>1 year, Bos taurus breed, and those raised under intensive farming system exhibited a higher seroprevalence to T. evansi (P < 0.05). The results displayed a new alternative for antibody detection anti-T. evansi in livestock, using parasites propagated in vitro as antigen, which presents the advantage of higher standardization potential, and avoid the use of live animal for antigen production. A larger availability of this ELISA will generate useful information for a better understanding of the epidemiologic aspects, as well as for the management and control of these diseases in Colombia. However, the ability of the test to detect and/or cross react with T. vivax infections remains to be investigated. © 2019